A Hop Based Robust Routing Protocol in Wireless Sensor Network - Suresh, D; Selvakumar, K (International Journal of Computer Sciences and Engineering, 2014)
Routing protocol design is an important research area in wireless sensor networks, reliability, low-cost and easy to maintain are design goals of WSN routing protocol, hop based routing protocol has been receiving extensive attention for its simple and effective design ideas. HBRRP (Hop Based Robust Routing Protocol for WSN) is proposed. In data transmission phase, HBRRP makes parents and siblings as forward selection; relying on a formula for evaluating the routing quality, routing mechanism has a comprehensive consideration of the forward selection trigger update mechanism is used to maintain dynamic network topology. Exploiting the intuition that a less dynamic route lasts longer, we propose a new metric, the Route Fragility Coefficient (RFC), to compare routes. RFC estimates the rate at which a given route expands or contracts. Expansion refers to adjacent nodes moving apart, while contraction refers to their moving closer. RFC combines the individual link contraction or expansion behavior to present a unified picture of the route dynamics.